Real-time alert notification system for optimizing manufacturing production line via mobile application - Emran, Nurul Akmar; Harum, Norharyati; C.C., Yu; Ridzuan, M. M.; AlQubaisi, A.J. (Penerbit UTeM, 2024)
The existing system employed by Konica Minolta for handling emergency text alerts is ineffective and lacks reliability. The company, which specializes in business and industrial imaging solutions, relies on email notifications for daily emergencies. This approach has several drawbacks, as notifications are sent to all employees simultaneously, leading to irrelevant alerts for those not involved in the specific projects. Additionally, the visibility of these notifications raises concerns about confidentiality and privacy, potentially compromising sensitive information. As the volume of notifications increases, tracking and analyzing content becomes increasingly challenging. The objective of the Mobile Alert Notification System for Manufacturing Production Lines (MANSMPL) is to provide targeted alerts tailored by incorporating the role-based access control (RBAC) method specifically for manufacturing environments. To validate the identified problems, unstructured interviews and surveys with domain experts were conducted. The findings from the interviews and surveys were instrumental in designing MANSMPL. The developed application effectively streamlines the notification process, ensuring that alerts are relevant to the intended recipients. MANSMPL offers a novel solution that is tailored to a manufacturing environment that restricts alerts to intended recipients while maintaining the confidentiality and privacy of sensitive information.